Multi‐dimensional analysis identifies an immune signature predicting response to decitabine treatment in elderly patients with AML. (1st October 2019) - Zhao, Chenchen; Jia, Bei; Wang, Ming; Schell, Todd D.; Claxton, David F.; Ehmann, W Christopher; Rybka, Witold B.; Mineishi, Shin; Naik, Seema; Songdej, Natthapol; Sivik, Jeff M.; Hohl, Raymond J.; et al.
Summary: Decitabine is a DNA‐hypomethylating agent that has been widely applied for the treatment of acute myeloid leukaemia (AML) patients who are elderly or unfit for intensive therapy. Although effective, the complete response rate to decitabine is only around 30% and the overall survival remains poor. Emerging data support that regulation of DNA methylation is critical to control immune cell development, differentiation and activation. We hypothesize that defining how decitabine influences the immune responses in AML will facilitate the development of novel immune‐based leukaemia therapeutics. Here, we performed phenotypic and functional immune analysis on clinical samples from AML patients receiving decitabine treatment and demonstrated a significant impact of decitabine on the immune system. T‐cell expression of inhibitory molecules was upregulated and the ability of CD8 T cells to produce cytokines was decreased upon decitabine treatment. Importantly, in an unbiased comprehensive analysis, we identified a unique immune signature containing a cluster of key immune markers that clearly separate patients who achieved complete remission after decitabine from those who failed to do so. Therefore, this immune signature has a strong predictive value for clinical response. Collectively, our study suggests that immune‐based analyses may predict clinical response to decitabine and provide a therapeutic strategy to improve the treatment of AML.